Increased cardiac arrest survival and bystander intervention in enclosed pedestrian walkway systems. (September 2017) - Lee, Minha; Demirtas, Derya; Buick, Jason E.; Feldman, Michael J.; Cheskes, Sheldon; Morrison, Laurie J.; Chan, Timothy C.Y.
Abstract: Background: Cities worldwide have underground or above-ground enclosed walkway systems for pedestrian travel, representing unique environments for studying out-of-hospital cardiac arrests (OHCAs). The characteristics and outcomes of OHCAs that occur in such systems are unknown. Objective: To determine whether OHCAs occurring in enclosed pedestrian walkway systems have differing demographics, prehospital intervention, and survival outcomes compared to the encompassing city, by examining the PATH walkway system in Toronto. Methods: We identified all atraumatic, public-location OHCAs in Toronto from April 2006 to March 2016. Exclusion criteria were obvious death, existing DNR, and EMS-witnessed OHCAs. OHCAs were classified into mutually exclusive location groups: Toronto, Downtown, and PATH-accessible. PATH-accessible OHCAs were those that occurred within the PATH system between the first basement and third floor. We analyzed demographic, prehospital intervention, and survival data using t -tests and chi-squared tests. Results: We identified 2172 OHCAs: 1752 Toronto, 371 Downtown, and 49 PATH-accessible. Compared to Toronto, a significantly higher proportion of PATH-accessible OHCAs was bystander-witnessed (62.6% vs 83.7%, p = 0.003), had bystander CPR (56.6% vs 73.5%, p = 0.019), bystander AED use (11.0% vs 42.6%, p < 0.001), shockable initial rhythm (45.5% vs 72.9%, p < 0.001), and overall survival (18.5% vs 33.3%, p = 0.009). Similar significant differences were observed when compared to Downtown. Conclusions: This study suggests that OHCAs in enclosed pedestrian walkway systems are uniquely different from other public settings. Bystander resuscitation efforts are significantly more frequent and survival rates are significantly higher. Urban planners in similar infrastructure systems worldwide should consider these findings when determining AED placement and public engagement strategies.